PHENOLIC COMPOUNDFROMTHE STEM BARK OF MANGGIS HUTAN (Garelnla baneana Mlq.) AND THEIR ANTIOXIDANT ACTIVITY Senyawa Fenol darl Kullt Satang Manggls Hutan (Garelnla baneana Miq.) dan Aktlvitas Antloksldannya - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
ABSTRACT A phenolic compoud, (-)-epicatechin,was isolated from the stem bark of Garcinia bancana. The structure of this compound was determined base on spectroscopic data such as including Uv, IR, 1-D, 2-D NMR, and comparison with the reported data. Biological activity of this compound at free radical scavenging activity by 1,1- diphenyl-2-picrylhydrazylradical (DPPH) and inhibitory xanthine oxidase(XO) activity showed that (-)- epicathechin active at two methods with ICsovalue 8.1 and 8.6 j.lg/mLrespectively. Keywords: phenolic, (-)-epicatechin,Garcinia bancana, DPPH,XO